Entrepreneurial mindset among students of Technical and Vocational Education and Training (TVET) institutions in Malaysia - Dahalan, Dzuhailmi; Alby, Jeffrey Lawrence D'Silva; Ismail, Ismi Arif; Mohamed, Nor Aini (Academic Research Publishing Group, 2018)
This article examines entrepreneurial mindset among the students of Technical and Vocational Education and Training (TVET) institutions under the Ministry of Higher Education Malaysia. The findings presented are a small part of the overall research data on the readiness of TVET students in Malaysia to venture into entrepreneurship. This quantitative study involves 1000 students from eight selected public TVET institutions in Peninsular Malaysia. Overall, the study finds that respondents’ level of entrepreneurial mindset is at a moderate level. Furthermore, there is a significant difference in the level of entrepreneurial mindset between the respondents at the certificate level and diploma level, the background of the family/parents who own businesses and otherwise, and also between the respondents who are involved and not involved in business activities. This study holds a positive view that there is potential in enhancing the entrepreneurial mindset of students in TVET institutions in order to generate as many job creators as possible. Hence, the study suggests that the Ministry and all relevant stakeholders to streamline the strategy of the Higher Education Insititution (HEI) Entrepreneurship Action Plan by focusing on the key growth factors of entrepreneurial mindset so that the target of new entrepreneurial talents among HEI students can be realised and also by taking into consideration the potentials of TVET students in Malaysia.